Development of a simple method for measuring tedizolid concentration in human serum using HPLC with a fluorescent detector. Issue 49 (10th December 2021) - Tsuji, Yasuhiro; Numajiri, Miki; Ogami, Chika; Kurosaki, Fumihiro; Miyamoto, Aoi; Aoyama, Takahiko; Kawasuji, Hitoshi; Nagaoka, Kentaro; Matsumoto, Yoshiaki; To, Hideto; Yamamoto, Yoshihiro
Abstract : Abstract: The objective of the present study was to develop a method to measure tedizolid (TZD) concentration for studying target concentration intervention, pharmacokinetics, and pharmacodynamics of TZD. We established a high-performance liquid chromatography-fluorescence detector assay to measure the TZD concentration in serum for clinical application. Chromatographic separation was carried out on a 5 μm octadecyl silane hypersil column 150 mm × 4.6 mm. The mobile phase consisted of 0.1 M phosphoric acid and methanol (60:40, pH 7.0). Detection was performed at 300 nm and 340 nm for the excitation and emission wavelengths, respectively. The average retention times of TZD and the internal standard were 12.9 and 8.8 min, respectively. High linearity was exhibited over a concentration range of 0.025 to 10.0 μg/mL for TZD ( R 2  > 0.999). The intra- and inter-assay accuracies of TZD were 99.2% to 107.0% and 99.2% to 107.7%, respectively. The lower limit of quantitation and the lower limit of detection for TZD measurement were 0.025 and 0.01 μg/mL, respectively. The extraction recoveries of TZD were 100.4% to 114.1%. The high-performance liquid chromatography method developed in this study could separate the analytes with a single eluent (isocratic system), within a total run time of 15 min. Both TZD and IS were well separated, without interference from the peaks. Sharp peaks were observed in the chromatograms; problems such as double peaks, shoulder peaks, and broadened peaks were not observed. The proposed method showed acceptable analytical performance and could be used to evaluate serum TZD concentrations in patients.